Safety of exercise for adults with thoracic aortic aneurysms and dissections - Jesse Li; Alexandra Boyd; Michael Huang; Joshua Berookhim; Siddharth K. Prakash (Frontiers Media S.A., 2022)
BackgroundCurrent guidelines for patients with thoracic aortic aneurysms or dissections (TAD) restrict vigorous exertion with the intention to prevent acute aortic dissections. However, a safe threshold for exercise intensity has not been established for TAD patients. In this study, we measured exertional changes in systolic and diastolic blood pressure during isometric and dynamic exercises in a cohort of TAD patients to determine safety of moderate intensity exercise.MethodsThirty-one adults with TAD and 14 controls were recruited from UTHealth outpatient clinics. All participants completed an exercise protocol consisting of two circuits of five moderate intensity exercises: hand grips, leg raises, bicep curls, stationary cycling, and wall sits. Blood pressure values were recorded during exercise using Spacelabs OnTrak Ambulatory Blood Pressure monitors. Perceived exertion during each exercise was measured using the Borg CR-10 scale.ResultsNo significant differences in the maximum exertional systolic pressure, diastolic pressure, or change from baseline was found between the TAD and control groups. Higher amounts of self-reported weekly moderate activity level (MAL) in TAD correlated with lower exertional SBP during exercise. Higher Borg scores were associated with a greater change in systolic pressure.ConclusionModerate intensity exercise is safe and feasible for many TAD patients. Our data confirms that the Borg score may be a useful proxy for exercise intensity. In this study, we establish a reproducible exercise protocol that can be adapted to create individualized exercise regimens for TAD patients as part of a care plan to improve long-term cardiovascular health.